Come My Staff, I Lean Upon You: The Use of Staves in the Ancient Egyptian Afterlife - Brown, Nicholas R..
Sticks are some of ancient Egypt’s most versatile tools, which functioned in many different ways and feature in a variety of scene types, including funerary and afterlife. Within these scenes, the deceased may be shown carrying the mdw staff and/or w3s scepter, sometimes in conjunction with an ‘nh sign and other insignia. Earlier studies have examined ancient Egyptian staves individually, though no former scholarship has exclusively examined how the mdw staff and w3s scepter function within the funerary rites of the deceased. The use of sticks as a tool in the transformative process of the deceased is the focus of the current study, with a particular emphasis on both textual and artistic representations.   doi: http://dx.doi.org/10.5913/jarce.53.2017.a009